2010
DOI: 10.1371/journal.pcbi.1000949
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework for Influenza Antigenic Cartography

Abstract: Influenza viruses have been responsible for large losses of lives around the world and continue to present a great public health challenge. Antigenic characterization based on hemagglutination inhibition (HI) assay is one of the routine procedures for influenza vaccine strain selection. However, HI assay is only a crude experiment reflecting the antigenic correlations among testing antigens (viruses) and reference antisera (antibodies). Moreover, antigenic characterization is usually based on more than one HI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(179 citation statements)
references
References 27 publications
2
175
0
2
Order By: Relevance
“…. To further address this question, we used antigenic cartography, which provides easily interpretable measures and visualization of multidimensional antigenic relationships and has previously been used to study antigenic differences in influenza virus strains (40,49). This analysis provided further support for the idea that within-host changes in the virus can equal or exceed those differences seen across successive outbreak strains, with the antigenic space between P.D302 and both GII.4-2006b (D ϭ 9.91) and P.D1 (D ϭ 9.15) being greater than the average between the consecutive outbreak strains used in this study (average D ϭ 4.98; range, 2.11 to 12.11), and mirrors the global difference between early GII.4 isolates (1987, 1997, and 2002) and contemporary strains (2006b, 2009, and 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. To further address this question, we used antigenic cartography, which provides easily interpretable measures and visualization of multidimensional antigenic relationships and has previously been used to study antigenic differences in influenza virus strains (40,49). This analysis provided further support for the idea that within-host changes in the virus can equal or exceed those differences seen across successive outbreak strains, with the antigenic space between P.D302 and both GII.4-2006b (D ϭ 9.91) and P.D1 (D ϭ 9.15) being greater than the average between the consecutive outbreak strains used in this study (average D ϭ 4.98; range, 2.11 to 12.11), and mirrors the global difference between early GII.4 isolates (1987, 1997, and 2002) and contemporary strains (2006b, 2009, and 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic cartography. We utilized multidimensional-scaling (MDS) approaches as described and implemented within the AntigenMap 3D software (39,40). The EC 50 blockade titers of various sera against a panel of VLPs were normalized to the maximum blockade titer of each serum, as well as to the maximum overall blockade titer across sera (normalization method 1 in AntigenMap 3D).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigenic maps were constructed using AntigenMap (http://sysbio.cvm.msstate. edu/AntigenMap) (33,34) HI assay results, polyPLA results suggested that subtype H3N2 swine IAVs did not react with the negative-control H1N1 virus and polyclonal antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The antigenic maps of H3N2 swine IAVs were constructed using AntigenMap (http://sysbio.cvm.msstate.edu/AntigenMap) and data derived from the HI assay or the polyPLA (33,34). The data entry with an HI titer of Ͻ1:10 or a ΔC T of Ͻ3.00 was determined as a low reactor for the data from HI or the polyPLA, respectively.…”
Section: Methodsmentioning
confidence: 99%